PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII6 SMP NEGERI 3 TAMBANG - Titi Andri; Jalinus Jalinus; Susda Heleni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve learning process and the student’s mathematics learning outcomes through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle. The research was conducted in class VII6 SMP Negeri 3 Tambang in the odd semester of the academic year 2018/2019. The subject of this research consist of 29 students. The research instrument consists of learning materials used include Syllabus, Lesson Plan and Student Activity Sheets and instruments for collecting data are observation sheets and test of mathematics learning outcomes. Data analysis techniques in this study are descriptive narrative analysis and descriptive statistics analysis. From the analysis of observation sheets, it can be seen that there is improvement of learning process. The percentage and frequency of students who achieved minimum completeness criteria is increased from the basic score with percentage 34,48% (10 students) to cycle I with percentage 51,72% (15 students) and 79,31% (23 students) in cycle II. This research concludes that the implementation of PBL model improved the learning process and the student’s mathematics learning outcomes at class VII6 SMP Negeri 3 Tambang in the odd semester of the academic year 2018/2019.Key Words: Problem Based Learning model, Mathematics Learning Outcomes